Bollywood in Manila: the spectre of moral comparisons. Issue 4 (2nd October 2018) - Athique, Adrian; Lorenzana, Jozon
ABSTRACT: This article explores inter-Asian media reception using the example of Bollywood films and the setting of Metro Manila in the Philippines. Drawing upon a series of interviews and focus groups with both the existing audience and "unexposed" viewers from the "mainstream, " this study takes an interest in how audiences establish the "common ground" that allows them to decode Bollywood narratives. By rescaling the dynamics of inter-cultural media exchange from geopolitical competition down to the grassroots experience of ordinary people, this article demonstrates how Bollywood films provide the basis for imaginative comparisons that open up everyday affinities based on shared economic situations and moral dilemmas. Developing the further intuition that the comparative aspects of global imagination are felt as much as considered, this article seeks to demonstrate how the melodramatic form of Bollywood generates emotional responses that inculcate empathy and an ethic of care. Our larger purpose is twofold: firstly, to explore the potentials of inter-cultural exchange between two societies on opposite sides of "Asia" and, secondly, to encourage reflection upon the ways that mediation facilitates the comparative functions of the global imagination in everyday experience.